CREATING PKWTT CONTRACT AND IRRELEVANT COMPANY REGULATIONS REFRESHMENT OF CV. MASTER DINAMIKA PRAKARSA IN ACCORDANCE WITH THE LABOUR LAW) - Risko Fitriano; Windi Afdal (Universitas Internasional Batam, 2022)
Companies are places for profit or profit, and every company is founded on a legal basis. In order for workers and prospective workers to understand existing company regulations, companies need to formulate company regulations and work agreements, with company regulations and employment contracts, prospective workers and workers must comply with existing company rules, because company regulations are made based on existing facts or to minimize risks that will occur in a company. Establishment of company regulations so that we can comply with existing regulations and comply with company SOPs. The work agreement contains a binding agreement, in which the worker will work by receiving a wage order from the employer, and contains the terms of work as well as written and oral rights and obligations from both parties. The implementation of this community service uses an advocacy method to help partners (employers) improve their legal documents/agreements. The result of this community service is a draft PKWTT and a modernized draft of company regulations.